ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RUMAH SAKIT UMUM PUSAT HAJI ADAM MALIK MEDAN - Deddy Sepadha Putra Sagala (Jurnal Ilmiah Keperawatan IMELDA, 2019)
There are four factors that influence the quality of life patient with CRF will be discussed, i.e. the nutrition status, comorbid, duration of haemodialysis, and medical procedure. This research aims to study the dominant factor of the four factors that influence the quality of life patient with CRF. The sample in this research are the patients with CRF who underwent the haemodialysis at RSUP HAM Medan in the number of 32 patients. The sample was took by purposive sampling method. The method applied in this research is analytic descriptive method by using the instrument in the form of options would be check listed. The data is analyzed by using Pearson and Spearman correlation test and linear regression. The results of research indicates that (1) The Spearman correlation test for nutrition and quality of life obtain that r = 0.382 and p = 0.031 means that there is a significant correlation but is weak; (2) the Pearson correlation test for comorbid and quality of life obtain r = 0.568 and p = 0.001 means that there is a significant correlation but is medium; (3) Spearman correlation test for the duration of haemodialysis and quality of life obtain r = 0.106 and p = 0.291 means that there is not a significant correlation but is weak; (4) the Spearman correlation test for medical procedure and quality of life obtain r = -0.078 and p = 0.671 means that there is not a significant correlation and in opposed direction; (5) Linear regression test obtain the equation Y = 59.581 + 3.52X. Based on the results of study indicates that the comorbid condition is directly proportional to quality of life of patient with CRF that means that comorbid condition has an influence to the quality of life. Therefore it is important to optimize the nursing care to the comorbid condition in order to increase the quality of life patient with CRF either in the service or health education that support the health condition of patient.